Rapid change in small towns: when social capital collides with political/bureaucratic inertia. Issue 1 (1st January 2016) - Halseth, Greg; Ryser, Laura
Abstract: Successful community development is usually constructed with "bottom-up" capacity and "top-down" public policy. The synergy between these approaches has been hampered by the transition from a Keynesian to a neoliberal public policy framework. Under the stress of rapid change from major industrial projects, this article examines community development responses in the small town of Kitimat, British Columbia. Using a social capital lens, our findings suggest that despite limited senior government responses, local stakeholders have been using local and non-local network structures to: improve communication and understanding of protocols and procedures, improve awareness of community needs, access a broader range of financial and in-kind supports, transfer skills and broaden access to human resources, broaden access to infrastructure, and rapidly develop and deploy new supports. By formalizing network structures and working to strengthen local capacity, local stakeholders have been able to address many social and economic development pressures. Over the longer term, however, social capital and social cohesion among voluntary and non-profit sector organizations will require the assistance of senior government policy, financial, and program supports to be sustainable.